G-C3N4/g-C3N4 isotype heterojunction as an efficient platform for direct photodegradation of antibiotic. Issue 4 (3rd April 2018) - Wang, Yu; Qiao, Mengzhu; Lv, Jun; Xu, Guangqing; Zheng, Zhixiang; Zhang, Xinyi; Wu, Yucheng
ABSTRACT: A visible-light-driven g-C3 N4 /g-C3 N4 isotype heterojunction photocatalyst was synthesized by one-step thermal treatment using urea and thiourea as the precursor. The photocatalytic activity of as-prepared photocatalyst was evaluated through the degradation of rhodamine B (RhB) and tetracycline hydrochloride (TC) under the visible light irradiation. The hybrid showed enhanced photocatalytic activity in photodegradating the applied pollutants as compared with single g-C3 N4 . When the ratio of urea to thiourea was 2:1, the prepared isotype heterojunction exhibited the highest photocatalytic activity and the photodegradation rates for RhB and TC were 99.8% and 95.1% after being visible light irradiated for 1 h and 4 h respectively. The enhanced photocatalytic performance of the isotype heterojunction is ascribed to the enhanced charge separation efficiency. After being reused for 5 times, the hybrid still showed excellent recyclability and chemical stability. Furthermore, NaI, BQ and IPA were used as the sacrificial agents for studying the surface reactions in the photocatalytic process. The method used in this work provides a new pathway to achieve more efficient degradation of antibiotics and to stimulate further studies in this important field.